Indicator-based resilience assessment for critical infrastructures – A review. (April 2023) - Yang, Zhuyu; Barroca, Bruno; Weppe, Alexandre; Bony-Dandrieux, Aurélia; Laffréchine, Katia; Daclin, Nicolas; November, Valérie; Omrane, Khaled; Kamissoko, Daouda; Benaben, ‪Frederick; Dolidon, Hélène; Tixier, Jérôme; et al.
Abstract: A Safety Science focus on research in the science and technology of human and industrial safety. Critical Infrastructures (CIs), as a crucial part of urban technological systems, are highly correlated with urban safety management in terms of their resilience when cities are facing a crisis or disaster. According to many studies, indicator-based resilience assessment has been used frequently to manage CIs in recent decades. Defining and characterising indicators can be useful for managers of human and industrial safety, as it could help monitor and improve the capacities and performance of CIs. In recent years, critical infrastructures (CIs) have been damaged with increasing frequency (and will be so in the future) following natural or technological disasters. CIs, such as buildings, transportation networks and power systems, play an indispensable role in our society due to their importance for maintaining critical societal functions, economic organisation and national defence. Therefore, the popularity of "critical infrastructure resilience" has exploded in both academic and policy discourses. Indicator-based assessment is a convenient and common tool to help understand, analyse and improve CI resilience in the scientific field. This paper produces a state-of-the-art review of the existing indicator-based assessment of CI resilience. After a terminology presentation, which helps clarify the objective of this study, this paper will show: 1) two methods for selecting the current scientific papers applying indicators to assess CI resilience; and 2) analysis of the indicators in these papers based on the study objective. The results show that there are many indicators and they do not have a uniform standard system, which means an indicator system for CI resilience assessment must be established.